Counseling on Dynamic Stretching to Reduce Upper Trapezius Pain Complaints in the Kitchen Crew of Rampogan Matjan Restaurant, Malang City : Penyuluhan Dynamic Stretching Untuk Mengurangi Keluhan Upper Trapezius Pain Pada Kitchen Crew Rumah Makan Rampogan Matjan Kota Malang - Cevin Nugraha; Nurul Aini Rahmawati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Upper trapezius muscle pain is a common musculoskeletal issue caused by poor ergonomic posture. The kitchen crew at Rampogan Matjan Restaurant in Malang City are at high risk of experiencing this pain due to prolonged static postures without adequate stretching. Dynamic stretching is a physiotherapy intervention that improves flexibility, reduces muscle tension, and decreases pain levels. Health education on dynamic stretching was conducted to enhance kitchen crew members' understanding and awareness of workplace ergonomics and proper stretching techniques. The session included education on the causes of upper trapezius pain and a demonstration of dynamic stretching exercises. Evaluations through pre-test and post-test showed a significant improvement in participants' understanding. Knowledge about the causes of upper trapezius pain increased from 20% to 100%, while knowledge of dynamic stretching rose from 0% to 80%. Additionally, participants reported reduced pain levels after regularly practicing dynamic stretching. These findings indicate that health education on dynamic stretching is effective in increasing workers' awareness of workplace ergonomics and in preventing and reducing upper trapezius pain. Continuous education and the adoption of ergonomic work habits are necessary for long-term benefits.